Analisis Trade Transparency Unit dalam Mengatasi Trade Based Money Laundering di Amerika Serikat Tahun 2004-2016 - Nur Islamia Dewandani; Fendy Eko Wahyudi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
Trade Transparency Unit (TTU) cooperation was officially formed by the United States on 2004. The cooperation aimed to overcoming Trade Based Money Laundering (TBML) crime. This research aimed to analyze which factors most likely affected the formation of that cooperation (TTU). Quantitative research method was used in this research with independent variables such as GDP, Distance, Trade, membership of FATF and Egmont Group to the dependent variable TTU cooperation. By using the modification of gravity model and membership of international organizations toward TBML, this research obtained some results. That some independent variables such as GDP, Distance, Trade and membership of Egmont Group were significant to TTU cooperation meanwhile the membership of FATF was not significant to TTU cooperation.